War on the middle class : how the government, big business, and special interest groups are waging war on the American dream and how to fight back - Dobbs, Lou. (New York : Viking, 2006)
The middle class has never been so vulnerable. Its every feature is under assault by politicians and the lobbyists who court them, big-business corporations that are sending their jobs overseas, and a media that relies on sensationalism instead of facts when reporting the news. CNN host and commentator Dobbs looks at every aspect of the decline of the middle class--from a lack of political representation to America's corrupt health-care system--to demonstrate how the gap between America's newest haves and have-nots is no longer merely financial, but instead includes the erosion of education, employment, government, and community. Dobbs proposes a series of measures to resolve each issue and incite people, whose future is being mortgaged to benefit a powerful few, to preserve their rights and dreams.--From publisher description.
War on the middle class -- Class warfare -- The best government money can buy -- The politics of deceit -- He says, she says -- The exorbitant cost of free trade -- Exporting America -- Broken borders -- A generation of failure -- Health care: it's enough to make you sick -- The best of intentions -- Taking back America -- The Declaration of Independence -- The Constitution of the United States -- The Bill of Rights -- The Constitution: Amendments 11-27.
Includes bibliographical references (p. 253-267) and index.
Keywords: Middle class -- Government policy -- United States; Middle class -- United States -- Economic conditions; Pressure groups -- United States; Corporate power -- United States; Elite (Social sciences) -- United States; United States -- Economic policy -- 2001-2009.; United States -- Politics and government -- 2001-2009.